Pengaruh Kedisiplinan terhadap Prestasi Belajar Siswa Kelas X di MAN 1 Batu - Fanesha Dwi Hartono; Gwen Qotrunada (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aims to determine the influence of discipline on students’ learning achievement at MAN 1 Batu. Discipline is one of the key factors in the learning process, as a disciplined attitude encourages students to obey rules, manage their time effectively, and maintain consistency in studying. Students’ learning achievement is influenced not only by intellectual factors but also by non-intellectual factors such as attitudes, motivation, and discipline. This research employed a quantitative method with a correlational approach. The population consisted of all students at MAN 1 Batu, while the sample of 120 students was selected using random sampling technique. The research instruments included a discipline questionnaire validated by experts and documentation of report card grades to measure learning achievement. Data were analyzed using simple linear regression analysis with the assistance of statistical software. The results revealed a positive and significant influence of discipline on students’ learning achievement. The higher the level of student discipline, the better the academic achievement obtained. These findings highlight the importance of cultivating discipline in the school environment through regulations, teacher guidance, and parental support. Therefore, improving discipline can serve as an effective strategy to support students’ academic performance at MAN 1 Batu.